The Influence of Emotional Stress on Doppler‐derived Aortic Peak Velocity in Boxer Dogs. (13th October 2014) - Pradelli, D.; Quintavalla, C.; Crosta, M.C.; Mazzoni, L.; Oliveira, P.; Scotti, L.; Brambilla, P.; Bussadori, C.
<x xml:space="preserve">Abstract</x> Background Subaortic stenosis (SAS) is a common congenital heart disease in Boxers. Doppler‐derived aortic peak velocity (AoPV) is a diagnostic criterion for the disease. Objectives To investigate the influence of emotional stress during echocardiographic examination on AoPV in normal and SAS‐affected Boxers. To evaluate the effects of aortic root diameters on AoPV in normal Boxers. Dogs Two hundred and fifteen normal and 19 SAS‐affected Boxers. Methods The AoPV was recorded at the beginning of echocardiographic examination (T0), and when the emotional stress of the dog was assumed to decrease based on behavioral parameters and heart rate (T1). AoPV0–AoPV1 was calculated. In normal dogs, stroke volume index was calculated at T0 and T1. Aortic root diameters were measured and their relationship with AoPV and AoPV0–AoPV1 was evaluated. Results In normal dogs, AoPV was higher at T0 (median, 1.95 m/s; range, 1.60–2.50 m/s) than at T1 (median, 1.76 m/s; range, 1.40–2.20 m/s; P < .0001; reduction 9.2%). The stroke volume index at T0 also was greater than at T1 (P < .0001). Weak negative correlations were detected between aortic root size and aortic velocities. In SAS‐affected dogs, AoPV0 was higher than AoPV1 (P < .0001; reduction 7.3%). Conclusion and Clinical Importance Aortic peak velocity was affected by emotional stress during echocardiographic examination both in SAS‐affected and normal Boxers. In normal Boxers, aortic root size weakly affected AoPVs, but did not affect AoPV0–AoPV1. Stroke volume seems to play a major role in stress‐related AoPV increases in normal Boxers. Emotional stress should be taken into account when screening for SAS in the Boxer breed.